Pendidikan Literasi Keuangan Dalam Pembelajaran Ekonomi di SMA dan SMK Kabupaten Kubu Raya Kalimantan Barat - Ulfah, Maria; Kuswanti, Heni; Thoharudin, Munawar (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this study was to analyze financial literacy education in the Economic Learning of SMA and SMK in Kubu Raya Regency, West Kalimantan. The method used in this research was descriptive method with survey research form. This research was conducted at SMA and SMK in Kubu Raya Regency, West Kalimantan. The subjects of this study were teachers of economics subjects and principals or vice principal for curriculum of SMA and SMK in Kubu Raya Regency. The data collection technique used interview sheets and direct observation, while data analysis technique used descriptive analysis. Based on the results of research, it was found that 1) The material on defining economic transactions and various types of practice, introduction to economic resources, introduction to the concept of shopping. ) as a fulfillment of basic needs, introduction to the concept of saving in traditional and modern terminology, introduction to the concept of sharing (sharing) found in economic learning; 2) While the introduction to the concept of bad practices and financial crimes is not included in the syllabus of economic subjects, some teachers on their own initiative provide additional material on corruption to the students.